INTERVENSI GURU TERHADAP EKSPRESI TUTUR SISWA TUNARUNGU - Winarsih, Suko (LITERA, 2014)
This study aims to describe teacher interventions in deaf students' oral expressions, comprising those in speech acts, speech functions, and speech strategies. It employed the qualitative descriptive approach. The data comprised descriptive and reflective data. They were analyzed by means of pragmatics theory, especially clinical pragmatics. The findings are as follows. First, interventions in speech acts include illocutionary acts, conversation capabilities, understanding, and narration. Second, interventions in speech functions include directive and facilitative interventions. Third, interventions in speech strategies include context manipulation and pre-symbolic and minimum symbolic interventions.